E-PAC: efficient password authentication code based RMPN method and diffie-hellman algorithm - Salah H. Abbdal Refish; Salam Waley Shneen (Institute of Advanced Engineering and Science, 2020)
Users need more efficient and more secure when they use the Internet. Password authentication code (PAC) is the critical issue in many applications such as web-sites and data base systems etc. In this paper, PAC between two users to confirm authentication between them based two factors has presented.. Two factors is the most good solution in this field. A legitimate user needs to make sure about his partner to ensure their communication. So, this solution produces two important algorithms, the first one is utilized the Diffie-Hellman which considered the base of this work. The second is routing in message passing networks (RMPN) algorithm which determine the positions of bits which sent to specific party. The overall of this method convincingly to be more secure against both online and offline attacks. This scheme has some advantages such as secrecy of session key, password privacy, and mutual authentication. The performance and security analyses prove that the scheme is very efficient and mathematically immune for attackers.